A qualitative investigation to develop an adapted version of the EQ-5D-Y-3L for use in children aged 2–4 years - Dalziel, K; van Heusden, A; Sarvananthar, J; Jones, R; McGregor, K; Huang, L; Rivero-Arias, O; Herdman, M; Hiscock, H; Devlin, N (Elsevier, 2023)
Objectives: Few preference-weighted health-related quality-of-life measures exist for children under 5 years of age. Young children are substantial consumers of healthcare services. This project aims to assess EQ-5D-Y-3L’s appropriateness in children aged 2 to 4 years and to coproduce with parents a suitable adaptation. Methods: Purposive sampling at the Murdoch Children’s Research Institute and Royal Children’s Hospital was used to recruit parents or carers of children aged 2 to 4 years in Australia. Online focus groups were conducted consisting of 13 parents of healthy children, and 6 parents of children with moderate to severe health conditions. Parents provided feedback on each dimension of the proxy EQ-5D-Y-3L. Recordings were transcribed and thematic analysis was conducted. Qualitative findings guided the design of adaptations to the instrument. The adaptations were piloted to obtain feedback and refined to improve language translatability and comparability with other EuroQol instruments. Results: The adapted EQ-5D-Y-3L was considered generally acceptable by the parents. Parents provided a wide range of examples of how each domain related to their children, with varied examples provided across ages 2 to 4 years and health status. Additional or alternative wording was suggested by parents to improve the applicability of the instrument to this age group. One example of this was the change of the domain wording “walking about” to “movement”—ID5:“In this age group, movement is more important than walking.” Conclusions: The adapted EQ-5D-Y-3L has improved relevance for 2-4-year olds and appears easy to complete. Further testing of the adapted instrument is required to evaluate acceptability, reliability, and validity.